Corticosterone enhances formation of non-fear but not fear memory during infectious illness - Hill, Alice; Johnston, Colin; Agranoff, Isaac; Gavade, Swapnil; Spencer-Segal, Joanna (Frontiers in Behavioral Neuroscience, 2023)
Survivors of critical illness are at high risk of developing post-traumatic stress disorder (PTSD) but administration of glucocorticoids during the illness can lower that risk. The mechanism is not known but may involve glucocorticoid modulation of hippocampal- and amygdala-dependent memory formation. In this study, we sought to determine whether glucocorticoids given during an acute illness influence the formation and persistence of fear and non-fear memories from the time of the illness. We performed cecal ligation and puncture in male and female mice to induce an acute infectious illness. During the illness, mice were introduced to a neutral object in their home cage and separately underwent contextual fear conditioning. We then tested the persistence of object and fear memories after recovery. Glucocorticoid treatment enhanced object discrimination but did not alter the expression of contextual fear memory. During context re-exposure, neural activity was elevated in the dentate gyrus irrespective of fear conditioning. Our results suggest that glucocorticoids given during illness enhance hippocampal-dependent non-fear memory processes. This indicates that PTSD outcomes in critically ill patients may be improved by enhancing non-fear memories from the time of their illness.